Daerah Otorita Ibu Kota Negara: Koherensi Status Daerah Pada Ibu Kota Negara Nusantara Peraturan Perundang-Undangan Pemerintahan Daerah Di Indonesia - Ihsan Harivy Addas (UNES Law Review, 2024)
The dynamics of the discourse on relocating the national capital have been rolling after the Dutch colonization of Indonesia. This idea is not without reason, considering that the Indonesian government regime from the beginning had a long blue print in managing the government of the Republic of Indonesia and one of them was moving the capital city so that the Indonesian people had the authority to manage their territory while leaving the legacy of Dutch colonialization. Furthermore, Article 5 of Law number 3 of 2022 describes the specificity and position of the archipelago's capital city as an authoritative region. This has become a complex debate in academic discourse, especially in the field of constitutional law, considering that this law is substantially incoherent with the 1945 Constitution of the Republic of Indonesia article 18. Therefore, this article will further explain in more detail about the coherence of the status of “region” in the National Capital of the archipelago (IKN Nusantara). This article's research is based on normative legal research methodology or can also be referred to as doctrinal research. Normative research itself is one of the methods to find and determine what the law should be (ought to be) by analyzing various provisions of laws and regulations by presenting theories in legal science literature. Therefore, departing from the discourse on the relocation of the capital city and its implementation in Law number 3 of 2022, it is necessary to conduct a more specific study of the special regional status that is inline with the legislation that preceded it such as Law number 23 of 2014 as well as the 1945 Constitution of the Republic of Indonesia.